Abstracts (Edited by Prof. Tahir Mahmood) - Mahmood, Tahir (Pakistan Journal of Ophthalmology, 2006)
Quality-of-life improvements in cataract patients with bilateral blue light-filtering intraocular lenses. Espindle D, Crawford B, Maxwell A, Rajagopalan K, Barnes R, Harris B, Hileman K. J Cataract Refract Surg 2005; 31: 1952-9. Effect of postoperative refractive error on visual acuity and patient satisfaction after implantation of the Array multifocal intraocular lens Lee ES, Lee SY, Jcong SY, Moon YS, Chin HS, Cho SJ, Hyub Oh JH J Cataract Refract Surg 2005; 31:1960-65 Effect of preoperative counseling on patient fear from the visual experience during phacoemulsification under topical anesthesias Voon LW, Eong KGA, Saw SM, Verma D, Laude A. J Cataract Refract Surg 2005; 37:7966-9. Predicting patients' night vision complaints with wavefront technology Tuan KA, Chernyak D, Feldman ST. Am J Ophthalmol 2006; 141: 1-6. Comparison of three methods of measuring corneal thickness and anterior chamber depth Buehl W, Stojanac D, Sacu S, Drexler W, Findl O. Am J Ophthalmol 2006; 141: 7-12. Categorizing the stage of glaucoma from prediagnosis to end-stage disease Mills RP, Budenz DL, Lee PP, Noecker RJ, Walt J, Siegartel LR, Evans SJ, Doyle JJ. Am J Ophthalmol 2006; 141:24-30.